The Importance of Morphological/Physiological Heterogeneity as Adaptive Strategies in Stocks of Common Northern/Arctic Phytoplankton Species with Special Focus on the Common Diatom Chaetoceros socialis - Donnelly, Kathryn Anne-Marie (Universitetet i Tromsø, 2006)
The cosmopolitan, centric diatom Chaetoceros socialis was investigated in terms of its validity as a single species characterized by its morphology, physiology and distribution. A database was constructed using my own and published literature distribution observations of C. socialis in Northern Norway, the Atlantic, Arctic and Barents Sea. From this range of observations, it is possible to establish that C. socialis is found at temperatures ranging from -1.86°C to +13.6°C. Observations have been made between March and November with the greatest number of observations of C.Socialis being during March. Experiments were carried out under laboratory conditions with mono cultures of C. socialis grown at 2°C and 7°C. When cells were examined after cleaning, a significant difference in apical axis size was observed between cells which were grown at 2°C and those grown at 7°C. No significant difference was observed in growth rates between the cells grown at 2°C and 7°C. The morphology of the cleaned cells was observed to be different from the ‘standard’ or ’type’ for this species which leads one to question the present definition of C. socialis as a species.